A Philosophical and Comparative Legal Analysis of Amnesty: Lessons from Indonesia and the United States - Dwi Novantoro; I Gede Widhiana Suarda; Dominikus Rato; Bayu Dwi Anggono; Dinara F Abdunayimova (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2026)
Introduction: Amnesty occupies an uneasy position within contemporary legal systems, situated between the ideals of justice, mercy, and constitutional authority. While often justified as an extraordinary legal response to exceptional circumstances, its application continues to provoke concerns regarding legal certainty, equality before the law, and institutional accountability within modern constitutional democracies. Purposes of the Research: This article seeks to explore the philosophical foundations and legal justification of amnesty through a comparative analysis of its practice in Indonesia and the United States. It aims to examine how differing constitutional traditions conceptualise the legitimacy, limits, and moral implications of amnesty as a legal institution. Methods of the Research: The research adopts a normative legal methodology employing philosophical, statutory, and comparative approaches. Constitutional texts, legal doctrines, and theoretical perspectives are analysed through qualitative legal reasoning in order to assess the normative coherence of amnesty within each legal system. Results Main Findings of the Research: The findings indicate that although both Indonesia and the United States recognise amnesty as an extraordinary legal mechanism, they diverge significantly in terms of constitutional design, institutional safeguards, and moral justification. This article contributes by reframing amnesty not merely as an executive prerogative, but as a legal institution that demands philosophical accountability and constitutional restraint.